2019
DOI: 10.3389/fphar.2019.01445
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q0 From Antrodia cinnamomea Exhibits Drug-Resistant Bacteria Eradication and Keratinocyte Inflammation Mitigation to Ameliorate Infected Atopic Dermatitis in Mouse

Abstract: Atopic dermatitis (AD) is an inflammatory skin disease that is usually accompanied by Staphylococcus aureus infection due to cutaneous barrier-function damage. Benzenoid compounds from Antrodia cinnamomea are known to exhibit antibacterial and anti-inflammatory activities. This study sought to investigate the potential of benzenoids for treating bacteria-infected AD. The compounds were screened against methicillin-resistant S. aureus (MRSA). Coenzyme Q0 (CoQ0), a key ingredient in A. cinnamomea, showed the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…We developed psoriasis-like, AD-like, and photoaged skins in mice to analyze peptide delivery through inflamed skin. These inflammatory models were established in our previous reports and established a similar characteristic of histopathology with inflamed human skin [17,30,40,41]. All laser modalities enhanced the deposition of PT-1 into the psoriasiform and AD-like skins at a comparable level.…”
Section: Discussionmentioning
confidence: 79%
“…We developed psoriasis-like, AD-like, and photoaged skins in mice to analyze peptide delivery through inflamed skin. These inflammatory models were established in our previous reports and established a similar characteristic of histopathology with inflamed human skin [17,30,40,41]. All laser modalities enhanced the deposition of PT-1 into the psoriasiform and AD-like skins at a comparable level.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have shown that AC extracts have antibacterial and antiviral properties [ 16 , 17 , 18 ]. Therefore, the effect of ACEW diet supplementation on the inhibition of microbial growth in water was examined.…”
Section: Resultsmentioning
confidence: 99%
“…As a mainstream form of complementary and alternative medicine, traditional Chinese medicine (TCM) has been widely accepted for cancer patients because of its beneficial effects and lack of serious side effects 3 . Antrodia cinnamomea is a rare fungus that grows in Taiwan, China, distributing over broad-leaved forests at an altitude of 200–2000 m. Pharmacological studies have shown that A. cinnamomea has anti-tumor, liver protection, immune regulation, inhibiting vascular neointimal formation, lowering blood pressure and cholesterol, inhibiting platelet aggregation, and other physiological activities 4 , 5 , 6 , 7 , 8 , 9 . Of the numerous functions, the effects of hepatoprotective especially anti-HCC were the most often reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that A. cinnamomea contains a variety of physiologically active compounds, including terpenoids, adenosine, organic germanium, trace elements, proteins, ergosterol, vitamins, nicotinic acid, nucleic acid lectins, chitin, lignin, etc. 7 , 8 , 18 . However, current reports about the chemical fingerprint of A. cinnamomea are scattered, and the systematic study is lacking.…”
Section: Introductionmentioning
confidence: 99%